Quinine treatment of severe falciparum malaria in African children: a randomized comparison of three regimens. - Pasvol, G; Newton, C; Winstanley, P; Watkins, WM; Peshu, N; Were, J; Marsh, K; Warrell, D (1991)
The pharmacokinetics and effectiveness of three dosage regimens of quinine were studied in a group of 59 children with severe malaria. The children were randomized to receive high-dose intravenous or intramuscular quinine (20 mg salt/kg loading, then 10 mg salt/kg every 12 hr), or low-dose intravenous quinine (10 mg salt/kg loading, then 5 mg salt/kg every 12 hr). In the group receiving the high-dose intravenous regimen, mean high and low quinine concentrations were consistently greater than 10 and 6.5 mg/l, respectively. Peak concentrations as well as the time required to achieve them were similar in the intramuscular and high-dose intravenous groups. The low-dose intravenous quinine regimen resulted in mean peak concentrations greater than 6 mg/l and mean low concentrations greater than 3.5 mg/l. All blood concentrations exceeded the 99% in vitro inhibitory concentration (EC99) of 0.89 mg/l or less of quinine for 60 isolates of Plasmodium falciparum, which were taken from children with malaria during the same period. Judged by a number of clinical criteria, the response was better in patients receiving the high-dose than the low-dose intravenous regimen. The time taken to clear parasites with both the high-dose intravenous and intramuscular regimens were significantly shorter than those obtained in the low-dose group. We have also shown for the first time that the rate of parasite clearance can be directly related to the area under the quinine concentration versus time curve. This applied to all three quinine regimens (r = 0.4252, P less than 0.02; n less than or equal to 35). Five patients, two on the low-dose regimen, two on the intramuscular regimen, and one on the high-dose regimen, developed hypoglycemia after admission, but in these cases, insulin concentrations were correspondingly low. No significant quinine toxicity was observed in any of the cases. The high-dose intravenous quinine regimen described here may be optimal for treatment of severe falciparum malaria in areas of chloroquine resistance in Africa. Our data provide no justification for reducing the dose of quinine in the treatment of severe malaria in Africa. The intramuscular regimen could provide a satisfactory alternative in areas where intravenous administration might be delayed or is impossible.